Some endemic methods of fish capture in Pasig River. - Navarro, Elpidio M. (Philippine Institute of Fisheries Technology, 1952)
The Marikina River which transverses the town of Pasig from North to South and the Pasig river which runs from east to west are the fishing grounds. The Marikina river is of variable depth, ranging from three fathoms from its mouth to about 3 kilometers to the interior and become shallower at it's course. During dry season, the Markina River is very clear and the current is only noticeable during the low and high tides. In rainy days the current is strong and water overflows it's bank and the water remains turbid almost throughout the year except during a long dry spell, when the clear salinity water of Manila Bay flows to the Laguna Lake. The current is strong throughout the year. Almost all species of fresh water fishes abound on these waters. The most abundant species are the catfish, mullets, gobies, ten pounders, spadefish, fresh water cray fish, carps, freshwater grouper and the climbing. Fishes caught are sold in the towns of Pasig and Marikina where they command better prices. There are many people fishing in these rivers. Most of them are catching fish for their own consumption. Fishing in these rivers is regulated and supervised by the municipalities concerned.